Sinergi Kewirausahaan Mahasiswa Universitas Merangin dan Kearifan Lokal: Solusi Inovatif untuk Pemberdayaan Masyarakat - Kusaimah; Dahri, Muhtar; Farhid Hidayah, Maoren (Vox Populi: Jurnal Umum Pengabdian Kepada Masyarakat, 2024)
Community empowerment through entrepreneurship based on local wisdom is a highly relevant approach to improving economic welfare at the village level. This article aims to explore the synergy between students of Merangin University and the potential of local wisdom in community empowerment. The study identifies various strategies for utilizing local wisdom, such as handicrafts, culinary products, and traditional goods, which can be developed into sustainable entrepreneurial ventures. In addition, the article discusses the importance of innovation in the development of local wisdom-based products and effective marketing strategies through digital platforms. The collaboration between universities, government, and communities, based on the Triple Helix concept, is seen as a key factor in accelerating the empowerment process and improving the local economy. This research uses a qualitative approach, with data collection through interviews, observations, and focus group discussions with the community and local entrepreneurs. The findings show that with proper innovation and collaboration, entrepreneurship based on local wisdom can have a positive impact on community economic empowerment.